Association between fibrinogen-to-albumin ratio and the presence and severity of coronary artery disease in patients with acute coronary syndrome - Zhenzhen Duan; Chaodi Luo; Bowen Fu; Dan Han (BMC Cardiovascular Disorders, 2021)
Abstract Objective Although the levels of plasma fibrinogen and albumin have been proven to be in relation to coronary heart disease (CHD), the association between fibrinogen-to-albumin ratio (FAR) and acute coronary syndrome (ACS) has not been adequately investigated. The aim of this study is to investigate the relationship between FAR and the presence and severity of CHD in patients with ACS. Methods and results A total of 1575 individuals who received coronary angiography (CAG) were enrolled. Patients were divided into the ACS group and the control group. The severity of ACS was determined by Gensini score, number of diseased coronary artery and the presence of myocardial infarction (MI). Data showed that the level of FAR in ACS group was higher than in the control group (81.20 ± 35.45 vs. 72.89 ± 20.24, P < 0.001). The results from subgroup analysis indicated that the values of FAR in the high Gensini score group, MI group and multiple-vessel stenosis group were higher than the matched subgroups. After adjustment for confounders, FAR was still independently related to the presence and severity of ACS (MI OR 2.097, 95%CI 1.430–3.076; High GS: OR 2.335, 95%CI 1.567–3.479; multiple-vessel disease: OR 2.088, 95%CI 1.439–3.030; P < 0.05). Conclusion The levels of FAR are independently associated with the presence and the severity of coronary artery disease in patients with ACS. Furthermore, FAR, as a more convenient and rapid biological indicator, may provide a new idea for predicting the presence and severity of ACS.